The impact of technological transformation on basic research results: The moderating effect of intellectual property protection - Xuhua Hu; Zuchong Zhang; Chengyang Lv (Journal of Innovation & Knowledge, 2023)
This study creatively investigates the strategic and substantive innovation transformation of basic research results from the perspective of intellectual property protection. Using Chinese provincial panel data from 2001 to 2018, the relevant empirical research findings are threefold. First, basic research results have a significant role in promoting strategic and substantive innovation, and the level of intellectual property protection has a significant regulatory role. Improved intellectual property protection will weaken the strategic innovation transformation of basic research results and strengthen substantive innovation transformation and a variety of robustness tests support these conclusions. Second, a regional heterogeneity test demonstrates that intellectual property protection has the most significant impact on the technological transformation of basic research results in the eastern region. Third, an industrial heterogeneity test indicates that intellectual property protection significantly enhances the substantive innovation transformation of high-tech enterprises, and the impact on general industrial enterprises is insignificant. The research findings provide a theoretical foundation and empirical evidence for China to improve its intellectual property protection system to facilitate basic research innovation transformation efficiency while comprehensively considering regional and industrial differentiation.